SPECTROPHOTOMETRIC STUDIES ON THE INTERACTION BETWEEN BENZOCAINE AND POLYMERS/MIXED POLYMER SYSTEM - Aisha Naz, Fauzan Badar,Farheen Rahman,Elham S. Aazam, S. M. Shakeel Iqubal, Aejaz A. Khan, Tasneem Mohammed, Areej Dawoud, Abdul Rahman Ikbal, KayamkaniAbedulla Khan, M.Z.A. Rafiquee (International Journal of Modern Agriculture, 2020)
The dynamical and morphological behaviour of PVP in presence of different additives was studied. Here-in we report the existence of different morphological arrangement and hydration states of PVP chain in aqueous medium. Interaction of benzocaine with PVP in presence of Sucrose, NaCl and Na2SO4effects the absorbance intensity (Amax) at λmax which is due to the extent of delocalization of pi electrons in the aromatic moiety. The variations in absorbance values at different concentrations of PVP were determined using highly hydrated salt like Na2SO4 the PVP-water interaction lessen up and promote more of the intra-chain PVP-PVP interaction. As a result, the PVP-PVP complex become more compact with the increase in concentration of Na2SO4 and in return its solubilizing capability for benzocaine increases as indicated by increase in Amax value. Interaction between Benzocaine and PVP-gelatin mixed system and Benzocaine PVP-starch mixed system results in dilation of PVP chains with coiling, encapsulation and solubilisation of benzocaine as indicated by the increase in Amax values.